Development of Constructivist Flipped Classroom to Enhance Students’ Creative Thinking for Designing Logo (International Conference on Computers in Education, 2016)
The purposes of this study were as follows: 1) To design and development of constructivist flipped classroom to enhance student’s creative thinking for designing logo, 2) To examine students’ creative thinking, and 3) To examine study student’s opinions. The target group of this research is grade 11 student of Pathumthep Witthayakarn School, high school in Thailand. The pre-experimental design, particularly with one shot case study was employed in this study. The research instruments were constructivist flipped classroom to enhance creative thinking on logo design with Adobe Illustrator CS6, creative thinking test form, and opinions survey form. The results revealed that: 1) The designing of constructivist flipped classroom consisted of the following components; (1) Problem Base (2) Resources (3) Creative Thinking Room (4) Collaboration (5) Scaffolding and (6) Coaching. 2) The creative thinking was found from the creative thinking test form ( X = 31.59 and S.D. = 1.67) that every learner passes the 70% criterion of the specific scores. 3) The students’ opinion towards the constructivist flipped classroom was divided into 3 aspects. They were 1) the contents can be supported concept formation of the learners, 2) characteristic of constructivist flipped classroom was designed for helping learners to easily for learning about in classroom and out of the classroom, 3) the constructivist flipped classroom supported and encouraging learners to enhancing knowledge construction and creative thinking; fluency, flexibility, originality and elaboration.